Hindu Religious Practices in Pregnancy Care for Stunting Prevention among Hindu’s Family in Kupang City - Dewa Putu Sahadewa; Ida Bagus Gde Yudha Triguna; I Made Damriyasa (UNHI PRESS, 2025)
This study examines the influence of Hindu religious practices on prenatal care and stunting prevention among Hindu families in Kupang City, East Nusa Tenggara. Despite the region's high stunting prevalence, Hindu families exhibit significantly lower rates. To understand this disparity, the research employs a qualitative methods approach, incorporating in-depth interviews, observations, and a textual analysis of relevant Hindu scriptures. By delving into specific practices like magedong-gedongan, this study aims to identify cultural factors contributing to improved maternal and child health outcomes. Hindu practices, such as magedong-gedongan, offer valuable prenatal education and socio-cultural bounding , while banten and prasadham provides nutritional guidance. Additionally, the ceremonial aspects and daily prayers contribute to optimal physical , psychological and mental well-being, essential for stunting prevention. The findings of this study may inform culturally sensitive public health interventions and programs to address stunting, especially in this region